Antibodies Against Enteric Bacteria in Brown Bullhead Catfish (Ictalurus nebulosus, LeSueur) Inhabiting Contaminated Waters - Troast, Judith L. (1975)
Brown bullhead catfish were collected from sewage- and acid mine waste-polluted waters in an attempt to detect antibodies against human enteric bacteria in their sera and to investigate the association of antibody response with environmental conditions. Agglutination antigens prepared from isolates obtained from water collected at the same locations as the fish habitats were used to demonstrate such antibodies. The results showed large percentages of reactive sera for common isolates such as Escherichia coli and Enterobacter cloacae as well as lesser incidences of antibodies to other, less common isolates. In general, fish with the highest titers were collected from habitats with higher coliform counts. Acid mine drainage reduced the total coliform counts, but did not appear to affect the titers of sera from fish collected from water so affected. It was concluded that the bottom-feeding catfish might be a better subject for the study of fish as an ecological indicator of fecal pollution in acid-polluted waters.